2022
DOI: 10.1093/gerona/glac090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Power Training on Cognitive Function in Older Adults With Type 2 Diabetes: Secondary Outcomes of the GREAT2DO Study

Abstract: We sought to determine the effects of 12 months of power training on cognition, and whether improvements in body composition, muscle strength and/or aerobic capacity (VO2peak) were associated with improvements in cognition in older adults with type 2 diabetes (T2D). Participants with T2D were randomized to power training or low intensity sham exercise control condition, three days per week for 12 months. Cognitive outcomes included memory, attention/speed, executive function, and global cognition. Other releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…There is no study showing a mediating effect of cardiorespiratory fitness on cognitive performance in T2D, but we previously showed that fit obese individuals have better cognitive performances compared to their unfit obese peers, and have similar cognitive performances to those of non-obese controls [ 23 ]. Memory performance was associated with body composition changes in previous studies in T2D [ 45 ]. Strategies to improve both cardiorespiratory fitness and cognition have been proposed, such as exercise training [ 46 ].…”
Section: Discussionmentioning
confidence: 81%
“…There is no study showing a mediating effect of cardiorespiratory fitness on cognitive performance in T2D, but we previously showed that fit obese individuals have better cognitive performances compared to their unfit obese peers, and have similar cognitive performances to those of non-obese controls [ 23 ]. Memory performance was associated with body composition changes in previous studies in T2D [ 45 ]. Strategies to improve both cardiorespiratory fitness and cognition have been proposed, such as exercise training [ 46 ].…”
Section: Discussionmentioning
confidence: 81%
“…DRT had a frequency of 2.9 ± 1.2 times per week, at moderate to vigorous intensity (n = 6), a volume of 6.1 ± 3.3 exercises, 3.2 ± 0.7 sets, 11.2 ± 3.6 repetitions for 25.14 ± 16.12 weeks with a mean adherence of 85.85%±10% (n = 6). The number of studies reported FIVDP was 5 (128,129,131,132,134).…”
Section: T2dmmentioning
confidence: 99%
“…The major outcomes varied among seven studies, including muscle quality and muscle strength (128), glycemic control (129,130), in ammation and endothelial function (131), physical performance (132), muscle strength (133), and cognition (134). Four of them found signi cant improvement in the major outcomes (128)(129)(130)132).…”
Section: T2dmmentioning
confidence: 99%
See 1 more Smart Citation